Acute Alcohol-Induced Liver Injury - Arteel, Gavin E. (Frontiers in Physiology, 2012)
Alcohol consumption is customary in most cultures and alcohol abuse is common worldwide. For example, more than 50% of Americans consume alcohol, with an estimated 23.1% of Americans participating in heavy and/or binge drinking at least once a month. A safe and effective therapy for alcoholic liver disease (ALD) in humans is still elusive, despite significant advances in our understanding of how the disease is initiated and progresses. It is now clear that acute alcohol binges not only can be acutely toxic to the liver, but also can contribute to the chronicity of ALD. Potential mechanisms by which acute alcohol causes damage include steatosis, dysregulated immunity and inflammation and altered gut permeability. Recent interest in modeling acute alcohol exposure has yielded new insights into potential mechanisms of acute injury, that also may well be relevant for chronic ALD. Recent work by this group on the role of PAI-1 and fibrin metabolism in mediating acute alcohol-induced liver damage serve as an example of possible new targets that may be useful for alcohol abuse, be it acute or chronic.